Monte Carlo sampling for the tourist trip design problem - Xiaochen Chou (Instituto Politécnico de Viseu, 2019)
Introduction: The Tourist Trip Design Problem is a variant of a route-planning problem for tourists interested in multiple points of interest. Each point of interest has different availability, and a certain satisfaction score can be achieved when it is visited.